From plate to waste: a cross-sectional study of food waste trends in Al Ahsa, Saudi Arabia - Al Khatib, Alissar; Hassanein, Salwa; Abdrbo, Amany; Almari, Mohammed; AL-Turaiki, Sommanah M.; Alkhunaizi, May; Antar, Ahmad (Frontiers in Sustainable Food Systems, 2024)
Background Food waste is a global concern that needs special attention and urgent actions to reduce the amount of wasted food. This study aims to investigate the trend of food waste in Al Ahsa. Methods This is a cross-sectional study designed to analyze the factors associated with the generation of wasted food within Al Ahsa community. Results The results showed that out of 257 participants, 82.9% were of Saudi nationality, 83.3% were females, 69.6% below 34 years and the family sizes mean was around 6. The majority of study participants were unemployed (62.3%), the employed ones were in healthcare field (56.4%). No significant gender differences was found in terms of other food waste-related variables. No significant association was found with age and occupation. Non-Saudi participants significantly report a lower frequency of wasting food and a higher rate of attitudes toward food waste sorting with p = 0.02 and p = 0.02, respectively. Working participants showed significant differences in terms of attitudes toward food waste sorting (p = 0.002), attitudes toward reducing food waste (p = 0.042), and the amount of food wasted per day (p = 0.010) when compared to those who are not working. Doctorate level of education exhibited significant (p = 0.002) attitudes toward food waste sorting and those who are in the commerce field of education had higher mean scores (M = 2.81, SD = 0.84) to reduce food waste. The cause of food waste was related to expiry date (61.1%). The common cause of wasting food when eating out or ordering online, was related to participants’ preference for trying a variety of dishes (40.1%). The participants adherent to home-cooked food during pandemic (mean 3.85, SD 1.40). Males reported a slightly higher impact of COVID-19 on their dietary habits when compared to females (p = 0.04). The majority of participants agreed that sharing food with neighbors decreases food waste (Mean = 3.96, SD = 1.32). Moreover, they do not throw food due to religious and cultural beliefs (Mean = 3.36, SD = 1.60). Conclusion Creating educational campaigns, promoting sustainable waste management and integrating technology to reduce food waste are recommended to achieve Saudi vision 2030.